An elderly patient with depression and a suicide attempt during the COVID-19 pandemic: a case report - Mohd Salleh Sahimi, Hajar; Midin, Marhani; Lim, Jane Tze Yn; Anwar, Mohd Wafiy Ariffin; Abdul Samad, Farah Deena; Mohamad Kamal, Nurul Ain (Frontiers in Psychiatry, 2023)
Abstract Objective: Elderly individuals are among the age groups with the highest risk of suicide. The coronavirus (COVID-19) pandemic forces isolation and causes an increased risk of depression, hopelessness, and perceived burdensomeness among the elderly, increasing the risk of suicide. Method: This is a case report of an elderly single retired school principal with obsessive-compulsive personality traits who developed depression with psychotic symptoms after being isolated during the movement restriction order during the COVID pandemic. The social isolation led to feelings of loneliness, and hopelessness. The patient’s depressive symptoms worsened after he developed physical illnesses such as eye floaters which affected his daily activities. This caused him to have suicidal ideation to the extent that he attempted suicide by ingesting 90ml of pesticide. Two weeks prior to the attempt, he made attempts to update his will and ask his friend to keep it. After the suicide attempt, he vomited, had diarrhea and epigastric pain, and called his friend who brought him to the hospital Emergency Room (ER). He was resuscitated and subsequently admitted to the Intensive care unit (ICU). After being medically stabilized, he was transferred to the psychiatric ward where further treatment was given for his depression. His depressive symptoms and suicidal ideations improved after given antidepressants and psychotherapy. Result: The impact of the COVID pandemic has led to a surge in mental health issues such as anxiety and depression. The elderly are among the highest risk group of individuals to contract or die of COVID infection and also the highest to develop mental health issues related to the pandemic. On top of that, the risk of death by suicide is highest in this age group due to physical illness, social isolation and lack of support system. This case also highlighted the need for awareness of suicidal ideation screening among non-medical healthcare professionals and religious organizations to avoid the treatment gap. Conclusion: It is essential to enhance suicide risk assessment and management among the elderly post-COVID-19 pandemic.